Effects of oral minoxidil on serum VEGF and hair regrowth in androgenetic alopecia - Kawen, Ahmed Abdulhussein (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Androgenetic alopecia (AGA) is a common hair loss condition characterized by follicular miniaturization. Vascular endothelial growth factor (VEGF) plays a key role in promoting angiogenesis and supporting hair follicle growth. Oral minoxidil has been suggested to upregulate VEGF levels, enhancing hair regrowth. Methods: This prospective study included 50 participants divided into two groups: oral minoxidil (1 mg/day; n = 25) and control (n = 25). Serum VEGF levels were measured at baseline and after 12 weeks of treatment. Hair growth parameters, including hair count, diameter, shedding, and pull test results, were assessed systematically. Results: Baseline VEGF levels were similar between groups (p = 0.1873). Post-treatment, VEGF levels increased significantly in the minoxidil group (217.88 ± 22.65 pg/ml vs. 142.81 ± 23.14 pg/ml in the control, p < 0.0001). Hair count and diameter improved significantly (p < 0.0001 and p = 0.0040, respectively), with reductions in shedding and pull test results (p < 0.0001). Positive correlations were observed between VEGF and hair count (r = 0.9965), whereas shedding showed negative correlations (r = -0.5374). Conclusions: Oral minoxidil significantly enhances VEGF levels, promoting hair growth and reducing shedding. VEGF serves as a promising biomarker for assessing treatment effectiveness and understanding the angiogenic mechanisms involved in AGA.
Keywords: androgenetic alopecia; androgenetska alopecija; angiogeneza lasnih mešičkov; hair follicle angiogenesis; hair regrowth; oral minoxidil; peroralni minoksidil; ponovna rast las; vascular endothelial growth factor; vaskularni endotelijski rastni faktor